The Batty Effect: Victim-Survivors and Domestic and Family Violence Policy Change - Wheildon, Lisa J. (Violence against women, 2022)
This article explores the influence of victim-survivors as change agents through the examination of the case of domestic and family violence advocate Rosie Batty. Utilizing public policy and criminological theories, and drawing from interviews with Batty and policy actors, the article examines the “Batty effect” and the convergence of factors that helped drive significant social and policy reforms in Australia. The article considers how Batty reflects characteristics of the policy entrepreneur and ideal victim, and how the sociopolitical context at the time provided the conditions for change. We conclude by exploring the implications for victim-survivor led policy change.